The effect of training in emotional intelligence through the self-science curriculum in a Lebanese elementary school context - Ajam, Dania Hassan (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2005)
The purpose of this study was to investigate the effectiveness of training Eleme ntary Grade 5 Lebanese students in Self-Science: The Emotional Intelligence Curr iculum, on the frequency of appropriate positive behaviors and inappropriate neg ative behaviors, and the Bar-On EQ-i: YV scores. In addition, to explore patter ns in the descriptive responses of the students, parents, and teachers about the students' behavior and Self-Science Program in general, and explore patterns in the students' emotional writing journal entries regarding expression of feeling s, demonstrating empathy, anger management, and applying the taught social probl em solving skills to daily life. The frequency of appropriate positive behavior s and inappropriate negative behaviors were measured by a behavioral observation checklist that was adapted from EQ rubric for assessment in Self-Science Curric ulum and the lessons to be taught from Self-Science Curriculum. The qualitative data was gathered using: open-ended evaluation response forms, informal teacher s' interviews, and students' emotional writing journals. The experimental group (n=18) received training in emotional intelligence skills through 30 sessions from Self-Science Curriculum, while control group (n=18) co ntinued instruction in their existing program of Homeroom time. The results of ANOVA conducted on the pre-training scores showed that the two gr oups were significantly different in average number of appropriate positive beha viors before exposing experimental group to the training in Self-Science Curricu lum. Therefore, ANCOVA was used in analyzing the posttest scores. ANOVA was us ed in analyzing the pre-training and post-training scores of the Bar-On EQ-i: YV . The results showed a significant increase in the average number of appropriate p ositive behaviors after exposing the experimental group to the training in Self- Science Curriculum. However, the results did not show a significant decrease in the average number of inappropriate negative behaviors after exposing the exper imental group to the training in Self-Science Curriculum, in comparison to the c ontrol group. Moreover, the scores on the Bar-On EQ-i: YV remained nearly the s ame for both groups. The qualitative data was analyzed by looking for patterns in the responses of the students, parents, and teachers, all of ...
: Mémoire
Keywords: Cycle primaire L enseignement des Sciences Curriculum; Elementary Education Sciences education Curricula; Emotional Intelligence; Intelligence Emotionnelle